Work Accident Analysis to Increase Work Productivity Using Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) Methods at PT. XYZ - Qurratul Aini; Rusindiyanto Rusindiyanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the important aspects that play a role in Increasing company productivity is work safety and security. Work carried out in workshops often causes work accidents. With this system, the company will be able to minimize the rate of work accidents, decreasing the accident rate and the severity of accidents from year to year will increase the productivity of the company's workforce. Based on this phenomenon, the purpose of this study is to determine work accidents and the effect of productivity on the workshop so as to increase work productivity and propose improvements to reduce work accidents in the workshop. The research was conducted by looking for the frequency of accidents, the severity of accidents, the tendency of accidents and the level of work productivity, and also using the FMEA and FTA methods. Based on the results of research on the level of work productivity in 2017, 2018, 2019, and 2020 of 0.0047; 0.0045; 0.0047; and 0.0051. In 2017 to 2018 it decreased, in 2018 to 2019 it increased by 4.44% and in 2019 to 2020 it increased by 8.52%. From the FMEA calculation, the highest RPN value was obtained, namely an accident that caused a torn hand with a value of 52 due to sleepy workers, lack of experience and lack of training. From the calculation of the FTA with a torn wrist accident, a probability of 0.03 is obtained. This figure shows that the accident is natural, if the probability is close to 1, the accident is unnatural and very dangerous and detrimental.